Today's teen - Kelly-Plate, Joan, 1935-; Eubanks, Eddye (New York : Glencoe, 1997)
Relationships, home management, money, grooming, housing, interior design, clothing, food, career selection and applying for a job form the main topics of this home economics textbook.
Includes index.
Keywords: Home economics; Family life education; Home economics